Metabolic cardiovascular risk profiles: a comparative study of khat-chewing and non-chewing women using hormonal contraception in Dhamar District, Yemen - Al-Anesi, Amat Al-Qader F.; Abhad, Abdul; Alans, Aziz; Alsumaiee, Jawaher M. A. N.; Hivrale, Vandana K. (International Journal of Research in Medical Sciences, 2026)
Background: The concurrent use of khat (Catha edulis) and hormonal contraceptives (HC) is common among Yemeni women, yet its combined effect on novel metabolic cardiovascular risk markers is poorly understood. This study compared the impact of khat chewing on serum homocysteine (Hcy), c-reactive protein (CRP), the atherogenic index of plasma (AIP), and lipid profiles in HC. Methods: A comparative cross-sectional study was conducted in Dhamar District, Yemen. One hundred women using HC were divided into 50 khat chewers and 50 non-chewers. Fasting blood samples were analyzed for Hcy, CRP, and lipid profiles, with calculation of AIP and (TC/HDL, LDL/HDL) ratios. Results: Khat-chewing women exhibited a significantly more adverse metabolic profile. Key findings included elevated diastolic blood pressure (75.80±12.14 versus 68.40±11.13 mmHg, p=0.002), higher homocysteine (7.81±2.55 versus 6.77±2.53 µmol/l, p=0.04), elevated CRP (4.88±1.25 versus 4.26±1.32 mg/l, p=0.01), lower HDL-C (46.58±8.06 versus 49.96±8.35 mg/dl, p=0.04), higher triglycerides (159.99±41.44 versus 141.17±19.58 mg/dl, p=0.005), and a substantially higher AIP (0.38±0.12 versus 0.30±0.094, p<0.001). A dose-response relationship was observed, with heavy use linked to greater disturbances. A significant interaction was found between khat and contraceptive type on atherogenic ratios. Conclusions: Among Yemeni women using hormonal contraception, khat chewing is a significant risk factor for an adverse cardiovascular profile, including hypertension, a pro-inflammatory and pro-thrombotic state, and atherogenic dyslipidemia. The harmful metabolic effects of khat were found to be modified by the type of contraceptive used. These effects also intensify with chewing duration, underscoring the critical need for targeted screening and personalized contraceptive counselling for khat-using women.